PDPN marks a subset of aggressive and radiation-resistant glioblastoma cells - Modrek, Aram S.; Eskilsson, Eskil; Ezhilarasan, Ravesanker; Wang, Qianghu; Goodman, Lindsey D.; Ding, Yingwen; Zhang, Ze-Yan; Bhat, Krishna P. L.; Le, Thanh-Thuy T.; Barthel, Floris P.; Tang, Ming; Yang, Jie; et al. (Frontiers in Oncology, 2022)
Treatment resistant glioma stem cells are thought to propagate and drive growth of malignant gliomas, but their markers and our ability to target them specifically are not well understood. We demonstrate that PDPN expression is an independent prognostic marker in gliomas across multiple independent patient cohorts comprising both high- and low-grade gliomas. Knock-down of PDPN radiosensitized glioma cell lines and Glioma Stem-like Cells (GSCs). Clonogenic assays and xenograft experiments revealed PDPN expression was associated with radiotherapy resistance and tumor aggressiveness. We further demonstrate that knockdown of PDPN in GSCs in vivo is sufficient to improve overall survival in an intra-cranial xenograft mouse model. PDPN therefore identifies a subset of aggressive, treatment-resistant glioma cells responsible for radiation resistance and may serve as a novel therapeutic target.